CLINICAL CHARACTERISTICS OF THREE COHORTS OF PATIENTS WITH EARLY- AND LATE-ONSET RHEUMATOID ARTHRITIS (AT 50 YEARS OR OLDER). GENERALIZATION OF 40 YEARS’ EXPERIENCE - A. M. Satybaldyev; N. V. Demidova; G. I. Gridneva; N. Yu. Nikishina; E. V. Gerasimova; D. A. Gukasian; K. A. Kasumova; E. L. Luchikhina; A. S. Misiyuk; T. G. Oskilko; O. A. Rumyantseva; E. A. Zlepko; et al. (Научно-практическая ревматология)
The paper presents three cohorts of patients with early rheumatoid arthritis (RA) who fell ill at 50 years or older and had a disease duration of 1.5 months to 1 year. To establish its diagnosis, the investigators used classification criteria for each cohort of its period: 1) the 1958 American Rheumatism Association (ARA) criteria; 2) the 1987 ARA criteria, and 3) the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria. Along with a change in the criteria, diagnostic methods were improved in this period. Many qualitative laboratory parameters were replaced with their quantitative equivalent; new disease markers (including anti-cyclic citrullinated peptide antibodies) emerged; imaging methods were improved; treatment policies were changed, and targeted biological agents and numerous analogs of the original drugs appeared.Conflicting opinions about the course of RA in older age groups have repeatedly been published in the literature. In the period when the 1958 classification criteria were applied, the opinion that RA has a relatively favorable course was prevalent. Later on, when a more rigid approach to diagnosing RA was applied, there were more and more specialists who considered it to be a severe disease. In this study, the authors try to answer the question of whether the course of the disease changed in the older age groups at the earliest possible date after its onset, by comparing the three cohorts of patients. The findings are discussed.